Child safety in policy: Who is being kept safe and from what?. (22nd March 2020) - Powell, Mary Ann; Graham, Anne; Canosa, Antonia; Anderson, Donnah; Moore, Tim; Robinson, Sally; Thomas, Nigel P.; Taylor, Nicola
Abstract: Keeping children safe from harm is a national policy priority in Australia. Extensive inquiries and reviews have highlighted institutions' persistent failures to respond ethically and appropriately to child abuse and its life‐long impacts on survivors. Policy efforts now reflect considerable emphasis on safeguarding children, including through the development of 'child safe' organisations. The realisation of these policy aspirations requires close attention to how 'child safe' is conceptualised and operationalised in different organisational contexts. Drawing on an analysis of policy in Australia and other international jurisdictions, namely New Zealand, the United Kingdom and Ireland, this article engages critically with the notion of 'child safe' in policy, to explore who is to be safe, from what and how, in organisational settings. The findings suggest emergent discourses of 'child safe' are bound up with particular constructions of both children and safety, reflect current social and political understandings and agendas, and have implications for organisations' approaches to safety. Ensuring the safety of children in Australia and other jurisdictions requires continuing scrutiny of policy implementation to make sure current policy efforts are not reduced to compliance‐based imperatives that protect organisations, but fail to create the cultural conditions that enhance children's wellbeing and safety.